Translation, cross-cultural adaptation, and validation of the Los Angeles Prehospital Stroke Screen for use in Brazil - Priscila Masquetto Vieira de Almeida; Rodrigo Bazan; Octávio Marques Pontes-Neto; César Minelli; José Eduardo Corrente; Gabriel Pinheiro Modolo; Gustavo José Luvizutto; Alessandro Lia Mondelli (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Stroke is one of the leading causes of death and neurological disability in the world. Several scales help professionals in the early recognition of the disease. However, none of these were developed in Brazil. Objectives: To translate the Los Angeles Prehospital Stroke Screen (LAPSS) into Brazilian Portuguese, and cross-culturally adapt and validate the scale in a representative sample of the Brazilian population. Methods: This study was carried out in two phases: the first consisted in the translation and cross-cultural validation of the LAPSS, and the second in a cross-sectional study with prospectively collected data in patients with suspected stroke treated in a Brazilian prehospital and referred to a stroke center. Statistical analysis was used to assess the sensitivity, specificity, and accuracy of the scale. Cohen's Kappa coefficient (κ) was used for psychometric assessment. Results: After translation and cross-cultural adaptation, the scale was applied to 86 patients. The scale presented a sensitivity of 83.8%, positive predictive value of 79.50%, specificity of 40.70%, negative predictive value of 47.80%, and accuracy of 77%. Cohen’s kappa coefficient was calculated using data from 26 (30.23%) patients and the results showed excellent inter-rater reliability in the majority of the items (52.96%). Conclusions: The scale was translated and cross-culturally adapted for use in Brazil. The scale presented high sensitivity and accuracy but low specificity, and the Cohen’s kappa demonstrated inter-rater reliability. The greatest difficulties occurred when the evaluation included subjective identifications. The scale excluded patients < 45 years old as stroke suspects.